ANALISIS PENGARUH PERUBAHAN DAN PERPUTARAN MODAL KERJA TERHADAP NET PROFIT MARGIN (NPM) PADA PABRIK KERTAS PT. TJIWI KIMIA TBK - Adawia, Popon Rabia; Azizah, Ayu; Rokhim, Abdul (Universitas Bina Sarana Informatika, 2019)
This research use 3 variable that is change of working capital and working capital turn as independent variable, Net Profit Margin (NPM) as dependent variable. The purpose of this study is to determine whether or not the influence of changes in working capital and working capital turnover to Net Profit Margin (NPM) at PT. Paper Factory Tjiwi Kimia Tbk. partially or simultaneously. To support the success of this study, collected secondary data in the form of balance sheet and income statement / loss PT. Paper Factory Tjiwi Kimia Tbk. from 2010 to 2016 and company documents relating to the research undertaken. Based on the results of research partially obtained the value of correlation (r) of 0.78 (strong) and 0.49 (enough) with t test results obtained value t arithmetic (t0) is smaller than t table (t0.11,612 and t0.2 0.799 <tcount 2.776), while the simultaneous test obtained r = 0.81 (very strong) with F arithmetic (F0) is also smaller than F table (F0 3.05 <Ftabel 6.94). So it can be concluded that the partial or simultaneous changes in working capital and working capital turnover has no positive and significant impact on Net Profit Margin (NPM) at PT. Paper Factory Tjiwi Kimia Tbk. Keywords: Change of working capital, working capital turnover and Net Profi Margin (NPM)